Analisis Kontribusi Sektor Industri Pengolahan Dan Pengaruh Bagi Hasil Pajak Terhadap Produk Domestik Regional Bruto (PDRB) Di Kabupaten Aceh Utara Tahun 2008-2017 - Sulaiman Sulaiman; Murtala Murtala (Jurnal Ekonomi Regional Unimal, 2021)
The purpose of this study was to determine the effect of tax revenue sharing (X) on GRDP (Y) in North Aceh District and find out the contribution of the manufacturing sector to GDP in North Aceh District. To achieve this goal, this study uses secondary data in the form of time series in 2008-2017 which are sourced from the North Aceh Regency BPS. A data analysis method using Simple Linear Regression and Analysis of GRDP Sector Contribution. The results showed that partially stated that tax revenue sharing had no significant effect on GRDP in North Aceh District. The contribution of the manufacturing sector to the GRDP in North Aceh District was the largest in 2015, which was 16% and the smallest occurred in 2008 at 4.09%. The average contribution of the manufacturing sector to the GRDP in North Aceh Regency over the past 10 years is 11.59%.